'An Epic Tale of England': Atmospheric authentication of nationalist narratives. (April 2022) - Shaw, Robert; Richardson, Michael J
Kynren is an outdoor spectacular pageantry performance which tells a tale of England, drawing on myth and history, to make several claims about Englishness and Britishness. It does so in the political wake, first, of constitutional crises in the UK centred around Brexit; and second, of debates around heritage, empire, race and nation which have been driven by responses to the Black Lives Matter movement. These themselves are manifestations of broader, global trends in which populist movements have attempted to reassert state-legitimacy through nationalism, heritage and culture. This paper explores, how Kynren affectively presents and discursively performs a narrative which puts place and landscape, and specifically the place and landscape of the peripheral region of County Durham in which it is located, at the heart of nation. We argue that the ways in which this narrative is authenticated performatively through the spectacular affective atmosphere of Kynren show how and which nationalist narratives resonate most readily in popular culture.